Estimasi Parameter Genetik Sifat Produksi Sapi Simmental di Balai Pembibitan Ternak Unggul Sapi Potong Padang Mengatas, Sumatera Barat (Estimation of Genetic Parameters of Production Characteristics on Simmental Cattle at Balai Pembibitan Ternak Unggulan - Hary Suhada; Sumadi (Sumadi); Nono Ngadiyono (Buletin Peternakan, 2009)
The objectives of this research were to estimate the genetic parameters of production characteristics, breeding value (BV), weaning weight ratio (WWR) correlation with BV and most probable producing ability (MPPA) of Simmental cattle reared at Balai Pembibitan Ternak Unggul Sapi Potong Padang Mengatas. Research was based on records of birth weight (BW), weaning weight (WW), post weaning average daily gain (ADG) and yearling weight (YW) from 2002 to 2007. Heritability value (h2) was estimated for BV, WW, ADG and YW using paternal-half sib correlation and repeatability value (r) of characteristics of both using intra class correlation. The genetic correlation (rG) of BW-WW, WW-YW, WW-ADG, WW-YW, WW-ADG and YW-ADG were analyzed by variance and covariance. BV and MPPA estimation was base on record of weaning weight. The h2 value of BW, WW, YW and ADG were 0.11±0.09; 0.39±0.16; 0.43±0.19; and 0.46±0.20, respectively. The r of BW, WW, YW and ADG, were 0.25±0.16; 0.32±0.18; 0.25±0.22; and 0.34±0.16, respectively. The genetic correlation value of BW-WW, WW-YW, WW-ADG, WW-YW, WW-ADG and YW-ADG were 0.29±0.37; 0.46±0.33; 0.2 ±0.39; 0.68±0.16; 0.006±0.30 and 0.57±0.21, respectively. From 18 Bulls, 10 bulls (55.56%) had the BV higher then average population value, 142.21 kg and the remaining 8 bulls (44.44%) was lower then average population value. Frequency of the BV of prospective male and female with WW higher than WW average was 210 calves (44.68%); whereas, 260 calves (55.32%) had WW lower than average population corrected with parent age (130.21 kg). Range of absolute BV was from 112.77 kg to 155.91 kg. The BV of male had average frequency higher than that of female, i.e. 149 males (66.22%) compared to 61 female (24.90%). The MPPA with above the average WW of the population was 150 cows (41.67%) and the rest of cows (210 head or 58.33%) were under theaverage. The WWR had positive and significant correlation (1.00**) with the NP. It means that, if the cattle have a high WWR, they will also have a high NP, so that they can be used as the criteria of selection.(Key words: Simmental cattle, Genetic parameters, Breeding value, Most probable producing ability, Weaning weight ratio)